Inducible and combinatorial gene manipulation in mouse brain - Dogbevia, Godwin K.; Marticorena-Alvarez, Ricardo; Bausen, Melanie; Sprengel, Rolf; Hasan, Mazahir T. (Frontiers in Cellular Neuroscience, 2015)
We have deployed recombinant adeno-associated viruses (rAAVs) equipped with tetracycline-controlled genetic switches to manipulate gene expression in mouse brain. Here, we show a combinatorial genetic approach for inducible, cell type-specific gene expression and Cre/loxP mediated gene recombination in different brain regions. Our chemical-genetic approach will help to investigate ‘when’, ‘where’ and ‘how’ gene(s) control neuronal circuit dynamics, and organize, for example, sensory signal processing, learning and memory, and behavior.